A sustainable and green route to furan-2, 5-dicarboxylic acid by direct carboxylation of 2-furoic acid and CO2. Issue 48 (June 2021) - Wang, Yu-Gao; Guo, Chong-Yang; Shen, Jun; Sun, Yu-Qin; Niu, Yan-Xia; Li, Peng; Liu, Gang; Wei, Xian-Yong
Highlights: Carboxylation involved hydrogen abstraction in 2-furoate and electrophilic addition of CO2 . Hydrogen abstraction of furan ring was rate-determining. Selective generation of 2, 5-FDCA depended on hydrogen abstraction step and molecular features of 2-furoate. Abstract: Chemical utilization of CO2 via carboxylation has attracted increasing attention in the field of synthesizing carboxylic acids. As the most promising substitute for terephthalic acid, 2, 5-furandicarboxylic acid (2, 5-FDCA) is a bio-based platform compound with wide application prospects. 2, 5-FDCA could be sustainably and economically produced by direct carboxylation of 2-furoic acid (a biomass-derived raw material) and CO2 over Cs2 CO3 catalysis. In this paper, the effect of different reaction conditions on 2, 5-FDCA yield was investigated, and only generation of 2, 5-FDCA without 2, 4-FDCA or 2, 3-FDCA was determined by HPLC and GC/MS analyses of the resulting product mixtures. Furthermore, density functional theory (DFT) was used to gain deep insight into the mechanism of direct carboxylation reaction. The reaction involved the hydrogen abstraction of furan ring in cesium 2-furoate (FA-Cs) by CO3 2− and subsequent CO2 electrophilic addition to form CC bond, and the former step was rate-determining for the reaction. More interestingly, the selective formation of 2, 5-FDCA relied on molecular features of FA-Cs during the hydrogen abstraction of furan ring.